Bennett, Karen; Queiroz de Barros, Rita (ed.). Hybrid Englishes and the Challenges of and for Translation: Identity, Mobility and Language Change - Antonio J. Martínez Pleguezuelos (Quaderns)
Bennett, Karen; Queiroz de Barros, Rita (ed.). Hybrid Englishes and the Challenges of and for Translation: Identity, Mobility and Language Change Londres / Nueva York: Routledge, 2019, 238 p. ISBN 978-1-138-30740-7